Remote measurement of sunflower seed moisture content by the use of microwaves. (5th May 2017) - Litvischenko, Vitali L; Nikiforov, Igor Ya; Ershov, Igor V
Abstract: BACKGROUND: Modern agriculture demands new methods and equipment that allow operators to conduct the instant control of moisture content over a wide area of agricultural fields with the purpose of providing farmers with the optimal moment of harvesting mature seeds and crops. Here the authors propose a new method and experimentally investigate the possibility to accomplish remote sensing of the moisture content of sunflower seeds using microwave radiation in the millimeter range. RESULTS: An experimental device for measuring the coefficient of reflection of electromagnetic waves from sunflower inflorescences in the frequency range 25.9–37.5 GHz was created. The obtained results showed that the moisture content of mature sunflower seeds affected the reflected signal. A difference in the reflected signal from the front and back sides of unripe sunflower inflorescences was also found. CONCLUSION: The results show that microwave radiation can be used to determine the degree of readiness of seeds for harvesting. The proposed new method opens up the possibility of remote instant diagnosis of sunflower seed ripeness in the field. © 2017 Society of Chemical Industry